Training And Implementation of Automatic Irrigation Systems for Grape Plants in Bangunsari Village, Tanjung Morawa District, Deli Serdang Regency, Sumatera Utara - Rudianto Surbakti; Citra Utami; Idham Kamil; Melvin Bismark Hamonangan Sitorus; Eka Putra Dairi Boangmanalu; Shuharzi Bin Md Salleh; Nurul Aimi Binti Ahmad Suandi; Mohd Fuaad Bin Fesul (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Rural development based on agrotourism is booming in Indonesia to increase community income. The process of cultivating grapes as an agrotourism has stages from land preparation, variety selection, proper watering care, to the process of picking and processing the harvest. The Bangun Sari village community has begun to develop grape cultivation as one of the agrotourism objects. However, due to limited human resources and technology, the productivity of agrotourism plants in Bangun Sari village has not been going well. The results of the grape plants that are currently cultivated are not optimal and many grape plants have not grown well because the irrigation and watering system is not good according to plant needs. International community service activities carried out by lecturers at the Medan State Polytechnic and in collaboration with the Nilai Negeri Sembilan Malaysia Polytechnic aim to implement automatic irrigation methods for grape farmers in Medan City. Community service activities begin with the presentation of material on automatic irrigation and watering systems followed by the fabrication and installation process of equipment in the field. The results of this community service activity are in the form of increased knowledge and delivery of products in the form of automatic irrigation and watering installations that have been installed at the grape cultivation location. The construction of this automatic fertigation equipment can solve farmers' problems. Ultimately, increasing the fertility and yield of grape plants can have an impact on increasing income.